Flow-generated displacement of reinforced granular slopes using the discrete element method - Dalaeli, Mozhdeh, author; Heyliger, Paul, advisor; Bareither, Christopher, committee member; Puttlitz, Christian, committee member (Colorado State University. Libraries, 2017)
The Discrete Element Method (DEM) has been used by researchers to study the behavior of granular material. It is based on the discrete nature of the granular media and tracks the displacements of individual particles and their interactions at every time-step of the simulation. This approach was used in this study to investigate the flow-generated displacement of spring-reinforced planar granular slopes. A Discrete Element (DE) code was created using MATLAB and FORTRAN to carry out the simulations. The code was validated by comparison of simulation results with analytical solutions. Granular slopes with particle radii ranging from 5 to 10 mm and various initial slopes were generated. Reinforced slopes were created by adding reinforcement, in the form of linear springs restraining surface particles, to the original geometry. The surface of both the original and the reinforced slopes was exposed to flow-generated drag forces. Various reinforcement patterns were modeled and the resulting flow-generated displacements were measured and studied. It was found that slope reinforcing can either delay or prevent flow-generated movements and the effectiveness of the reinforcing depends on the slope of the packing, size of the drag force and the pattern of the reinforcing.